Development of biosensors for detection of bacterial toxins and contaminants in complex food matrices - Klisara, Nevena (Nanyang Technological University, 2020)
This study attempts to merge novel sampling strategies and biomolecular sensing tools for the development of next-generation of rapid and sensitive bioassays for the detection of bacterial toxins and contaminants in complex food matrices. State of the art sampling, extraction and biosensor technologies are combined to develop prototype assays for onsite detection of toxins/proteases in contaminated food products. Considering the vast number of foodborne diseases and caused deaths, the assay for the fast and reliable analysis could assist in the early detection and subsequent prevention of foodborne illnesses. The conventional methodologies are tedious and cumbersome with requirements for trained personnel and expensive instruments. Thus, there is an urgent need to develop an on-site assay to meet requirements such as low cost, fast response, selective and sensitive with no need for sophisticated instrumentations.